2020
DOI: 10.1021/acs.orglett.0c03867
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Total Syntheses of Ergot Alkaloids via Decarboxylative Giese Coupling

Abstract: Biomimetic total syntheses of Festuclavine and Pyroclavine were achieved by a sequential radical coupling. The key steps include intramolecular decarboxylative Giese reaction to form the central C ring and 4-nitrobenzenesulfonyl (Ns)-directed indole C4–H olefination to introduce the indole C4 component. In addition, D-ring formation was completed by decarboxylative alkenylation and intramolecular SN2 reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…It was, however, revealed that the final products 6h–6j were unstable and rapidly decomposed after isolation. It is noteworthy to mention that attempts to deprotect the tosyl group on the amine moiety 6a under both basic conditions (4-OMePhSH/DIPEA) 20 and acidic conditions (TFA) 21 were unsuccessful, leaving the decomposition of the substrates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was, however, revealed that the final products 6h–6j were unstable and rapidly decomposed after isolation. It is noteworthy to mention that attempts to deprotect the tosyl group on the amine moiety 6a under both basic conditions (4-OMePhSH/DIPEA) 20 and acidic conditions (TFA) 21 were unsuccessful, leaving the decomposition of the substrates.…”
Section: Resultsmentioning
confidence: 99%
“…It was, however, revealed that the final products 6h-6j were unstable and rapidly decomposed after isolation. It is noteworthy to mention that attempts to deprotect the tosyl group on the amine moiety 6a under both basic conditions (4-OMePhSH/ DIPEA) 20 and acidic conditions (TFA) 21 were unsuccessful, leaving the decomposition of the substrates. To rationalize the proposed mechanism of this thiophosphorylation reaction, control experiments were performed to gain a mechanistic perspective on this synthetic transformation (Scheme 6).…”
Section: Papermentioning
confidence: 99%
“…All the chemicals like (R)-phenyloxirane and all other reagents were purchased commercially from Energy Chemical and used without further purification. NMR spectra were recorded on Bruker ADVANCE 400 ( 1 H 400 MHz, 13 C 100 MHz). Chemical shifts are reported in δ (ppm) relative to TMS in CDCl 3 as internal standard ( 1 H NMR) or the residual CHCl 3 signal ( 13 C NMR).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…After simple filtration and extraction, the collected organic phase was dried with MgSO 3.74 (m, 1H), 3.64 (ddd, J = 14.9, 6.6, 0.8 Hz, 1H), 3.54 (dd, J = 12.0, 10.4 Hz, 1H), 3.44 (dd, J = 11.4, 4.6 Hz, 1H), 3.25 (dd, J = 14.9, 11.8 Hz, 1H), 2.93 (dd, J = 12.0, 8.8 Hz, 1H), 2.65 (ddd, J = 16.9, 4.3, 3.1 Hz, 1H), 2.47 (s, 4H), 2.06 (d, J = 2.9 Hz, 1H), 2.05 (s, 6H). 13…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation